They receive antenatal care in health facilities, yet do not deliver there: predictors of health facility delivery by women in rural Ghana - Michael Boah (BMC Pregnancy and Childbirth, 2018)
Abstract Background Research has shown that use of antenatal services by pregnant women and delivery in health facilities with skilled birth attendants contribute to better delivery outcomes. However, a gap exists in Ghana between the use of antenatal care provided by health facilities and delivery in health facilities with skilled birth attendants by pregnant women. This study sought to identify the predictors of health facility delivery by women in a rural district in Ghana. Methods This was a cross-sectional study conducted in June 2016. Women who delivered in the past 6 months preceding the study were interviewed. Data on socio-demographic characteristics, use of antenatal care, place of delivery and reasons for home delivery were collected from study participants. Chi-square test and multiple logistic regression analysis were used to assess an association between women’s socio-demographic and obstetric characteristics and place of delivery at 95% confidence interval. Results The study found that 98.8% of women received antenatal care services at least once during their recent pregnancy, and 67.9% attended antenatal care at least four times before delivery. However, 61.9% of the women delivered in a health facility with a skilled attendant. The frequently mentioned reason for home delivery was “unaware of onset of labour and delivery”. The odds for delivery at a health facility were reduced among women with four living children [(AOR = 0.07, CI = 0.15–0.36, p = 0.001)], with no exposure to delivery care information [(AOR = 0.06, CI = 0.01–0.34, p = 0.002), who started their first ANC visit from the second trimester of pregnancy[(AOR = 0.003, CI = 0.01–0.15, p < 0.001)] and increased among women who made at least four ANC visits before delivery [(AOR = 17.53, CI = 6.89–44.61, p < 0.001)]. Conclusion Findings from this study revealed a low rate of delivery at health facilities although visits to antenatal care sessions were high, an indication that there was the need to intensify health education on early initiation of antenatal care, signs of labour and delivery, and importance of health facility delivery.